The Biopsychosocial-Digital Approach to Health and Disease: Call for a Paradigm Expansion - Ahmadvand, Alireza (J Med Internet Res, 2018)
Digital health is an advancing phenomenon in modern health care systems. Currently, numerous stakeholders in various countries are evaluating the potential benefits of digital health solutions at the individual, population, and/or organizational levels. Additionally, driving factors are being created from the customer-side of the health care systems to push health care providers, policymakers, or researchers to embrace digital health solutions. However, health care providers may differ in their approach to adopt these solutions. Health care providers are not assumed to be appropriately trained to address the requirements of integrating digital health solutions into daily everyday practices and procedures. To adapt to the changing demands of health care systems, it is necessary to expand relevant paradigms and to train human resources as required. In this article, a more comprehensive paradigm will be proposed, based on the ‘biopsychosocial model’ of assessing health and disease, originally introduced by George L Engel. The “biopsychosocial model” must be leveraged to include a “digital” component, thus suggesting a ‘biopsychosocial-digital’ approach to health and disease. Modifications to the “biopsychosocial” model and transition to the “biopsychosocial-digital” model are explained. Furthermore, the emerging implications of understanding health and disease are clarified pertaining to their relevance in training human resources for health care provision and research.